Increased Pathogen Identification in Vascular Graft Infections by the Combined Use of Tissue Cultures and 16S rRNA Gene Polymerase Chain Reaction - Ajdler-Schaeffler, Evelyne; Scherrer, Alexandra U.; Keller, Peter M.; Anagnostopoulos, Alexia; Hofmann, Michael; Rancic, Zoran; Zinkernagel, Annelies S.; Bloemberg, Guido V.; Hasse, Barbara K.; , and the VASGRA Cohort; Anagnostopoulos, A.; Hasse, B.; et al. (Frontiers in Medicine, 2018)
Background: Vascular graft infections (VGI) are difficult to diagnose and treat, and despite redo surgery combined with antimicrobial treatment, outcomes are often poor. VGI diagnosis is based on a combination of clinical, radiological, laboratory and microbiological criteria. However, as many of the VGI patients are already under antimicrobial treatment at the time of redo surgery, microbiological identification is often difficult and bacterial cultures often remain negative rendering targeted treatment impossible. We aimed to assess the benefit of 16S rRNA gene polymerase chain reaction (broad-range PCR) for better microbiological identification in patients with VGI. Methods: We prospectively analyzed the clinical, microbiological, and treatment data of patients enrolled in the observational Vascular Graft Cohort Study (VASGRA), University Hospital Zurich, Switzerland. The routine diagnostic work-up involved microbiological cultures of minced tissue samples, and the use of molecular techniques in parallel. Patient-related and microbiological data were assessed in descriptive analyses, and we calculated sensitivity, specificity, negative and positive predictive value for broad-range 16S rRNA gene PCR versus culture (considered as gold standard). Results: We investigated 60 patients (median age 66 years (Interquartile range [IQR] 59–75)) with confirmed VGI between May 2013 and July 2017. The prevalence of antimicrobial pretreatment at the time of sampling was high [91%; median days of antibiotics 7 days (IQR 1–18)]. We investigated 226 microbiological specimens. Thereof, 176 (78%) were culture-negative and 50 (22%) were culture-positive. There was a concordance of 70% (158/226) between conventional culture and broad-range PCR (sensitivity 58% (95% CI 43–72); specificity 74% (67–80%)). Among the group of 176 culture-negative specimens, 46 specimens were broad-range PCR-positive resulting in identification of overall 69 species. Among the culture and/or broad-range PCR-positive specimens (n = 96), 74 (77%) were monomicrobial and 22 (23%) polymicrobial, whereas the rate of polymicrobial samples was higher in broad-range PCR-positive specimens (93%). Conclusions: Combined cultures and broad-range 16S rRNA gene PCR from periprosthetic tissue and/or explanted vascular grafts increased the diagnostic accuracy in VGI, particularly in patients already under antimicrobial treatment at the time of redo surgery. Ideally, antimicrobial treatment should be withheld until surgical sampling in order to optimize microbiological diagnostics.Clinical trials.gov identifier: NCT01821664